The use of artificial intelligence tools and artificial intelligence generated content in debt collection and trends and developments for debt collection agencies to capitalise on - Dinklage, Andreea-Monica (2023)
Artificial Intelligence is on the rise, and is impacting various sectors, including the BPO and financial sector. This comes with opportunities of various natures, but also with challenges. The research question investigated in the report is how debt collection agencies can capitalise on the trends and developments and the use of artificial intelligence (AI) tools and AI-generated content (AIGC) to stay relevant, and to improve its business process to thus create gain an edge in the market. Debt collection agencies can thus enhance their customisation and increase the innovation created and delivered to their clients.